Application of Shariah Enterprise Theory on Disclosure of Corporate Social Responsibility in Sharia Banking - Eti Kusmiati; Ungkari, Marti Dewi (LPPM Universitas Terbuka, 2021)
The goal of this research is to find out what information Islamic banks provide in their corporate social responsibility reports, as well as to determine the acceptability of such material in terms of Shariah Enterprise Theory (SET). This study employed a qualitative research method using a case study methodology. Primary and secondary data are the two types of data used. Data reduction, data presentation, and verification are some of the data processing strategies employed. Findings. The findings of the research demonstrate that Bank Muamalat's CSR disclosures contained Sharia Enterprise Theory disclosure elements such as vertical and horizontal accountability, indicating that Bank Muamalat Indonesia has declared its social responsibility in a very informative manner.